2010
DOI: 10.1002/erv.1062
|View full text |Cite
|
Sign up to set email alerts
|

What are the top five essential features of a high quality eating disorder service? A comparison of the views of US and UK eating disorder sufferers, carers and health professionals.

Abstract: This study suggests many similarities and some differences between different stakeholders from two countries with different health care systems in their views on quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…All panels agreed that a patient's weight or presence of a comorbid medical condition should not be used as the sole indication for dietetic involvement, however, ED specialists were less likely to endorse automatic assessment or involvement by a dietitian compared to consumers/carers, or to agree about the how and when of any involvement. This result is consistent with a previous study which showed “nutritional assistance” during treatment was much more highly valued by ED consumers and carers compared to ED clinicians (Nishizono‐Maher et al, 2011). These findings indicate a potential barrier to the involvement of dietitians in ED treatment if access to dietitians is reliant on referrals being initiated by other members of a patient's treating team, some of whom may believe dietetic input will not make a valuable contribution to a patient's care.…”
Section: Discussionsupporting
confidence: 93%
“…All panels agreed that a patient's weight or presence of a comorbid medical condition should not be used as the sole indication for dietetic involvement, however, ED specialists were less likely to endorse automatic assessment or involvement by a dietitian compared to consumers/carers, or to agree about the how and when of any involvement. This result is consistent with a previous study which showed “nutritional assistance” during treatment was much more highly valued by ED consumers and carers compared to ED clinicians (Nishizono‐Maher et al, 2011). These findings indicate a potential barrier to the involvement of dietitians in ED treatment if access to dietitians is reliant on referrals being initiated by other members of a patient's treating team, some of whom may believe dietetic input will not make a valuable contribution to a patient's care.…”
Section: Discussionsupporting
confidence: 93%
“…Having said that, one previous quantitative study in ED found remarkable agreement between patients and therapists with regard to their views on effective aspects of treatment (Vanderlinden, Buis, Pieters, & Probst, ). Likewise, a survey focusing on what constitutes high‐quality ED services found remarkable agreement between different stakeholders (patients, carers and clinicians) (Nishizono‐Maher et al ., ). The overlap between patient and therapist experiences of MANTRA and SSCM will be discussed in the parallel patient experiences paper (Lose et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to these very positive views, many parents wanted more information on evidence for treatment and medications, and many parents wanted greater guidance in supporting their child to cope with weight gain and how to manage their own distress during treatment. Previous research has similarly identified a need for carer support in eating disorder services (22,23), which is especially relevant to FBT given the central role of parents. Since the survey was administered, a parent education and support group has been implemented at the current service (27).…”
Section: Discussionmentioning
confidence: 99%
“…Therapists surveyed in this study (n = 73) also valued these aspects but tended to place greater importance on the content of therapy than did patients (e.g., learning to eat normally, recovery of weight, improving body image). A similar study (22,23) surveyed patients (n = 196), carers (n = 79), and clinicians (n = 136) in the USA and UK. In that survey, patients rated the personal and professional qualities of the staff as the most important features of a high quality service, followed by the provision of psychological interventions.…”
Section: Introductionmentioning
confidence: 99%